Migration im 19. und 20. Jahrhundert - Oltmer, Jochen (Oldenbourg Verlag, 2013)
Migration im 19. und 20. Jahrhundert : Enzyklopädie deutscher Geschichte.
Keywords: Cultural pluralism -- North America.; Immigrants -- North America.; North America -- Emigration and immigration -- History.; Diversité culturelle -- Amérique du Nord.; Amérique du Nord -- Émigration et immigration -- Histoire.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; Cultural pluralism; Emigration and immigration; Immigrants; North America; Migration; Deutschland; History